The lone wolf threat posed by former JI members - Irfan Idris (2025)
The ideological influence of Jemaah Islamiyah continues to be a threat to security even after its disbandment in June 2024. Some of its former members may align with other extremist groups, while others may seek to operate as lone-wolf terrorists. The possibility of JI’s former members transitioning into lone wolf actors stems from the enduring power of its ideology and indoctrination process.